Percutaneous vertebral-disc plasty for thoracolumbar very severe osteoporotic vertebral compression fractures: A randomized controlled study - Jiang, Jiawei; Zhang, Jinlong; Bao, Guofeng; Chen, Jiajia; Wu, Chunshuai; Hong, Hongxiang; Xue, Pengfei; Xu, Guanhua; Cui, Zhiming (Frontiers in Surgery, 2022)
Purpose To compare the clinical outcomes and radiological parameters of patients undergoing percutaneous vertebroplasty (PVP) versus those undergoing percutaneous vertebral-disc plasty (PVDP) for back pain, segmental instability, and kyphosis due to thoracolumbar very severe osteoporotic vertebral compression fractures (vsOVCFs). Methods This prospective randomized controlled study included elderly patients with thoracolumbar vsOVCFs. All the patients were randomly allocated into the PVP group (who underwent conventional PVP) and the PVDP group (who underwent PVP combined percutaneous cement discoplasty). The visual analogue scale (VAS), Oswestry Disability Index (ODI), local kyphosis angle, and disc height were recorded preoperatively and postoperatively. Results Significant postoperative improvements in the VAS, ODI, and the local kyphosis angle (LKA) were shown, compared with the preoperative values in both groups (p < 0.05). The average VAS, ODI, and LKA for patients in the PVP group were increased compared to those in the PVDP group observed at the last follow-up (p < 0.05). The DHA, DHP, and LKA were seen to be maintained in the PVDP group at the last follow-up (p > 0.05). The change was significantly lower in the PVDP group at the last follow-up in those parameters (p < 0.05). Conclusion PVDP may be a feasible and effective technique for the treatment of very severe OVCFs, that can restore intervertebral height, provide segmental stabilizing and relieve back pain in the short term.